Ascertaining the financial loss from non-dependable events in business interactions by using the Monte Carlo method - Hussain, Omar; Dillon, Tharam S. (IEEE Computer Society, 2009)
Risk Assessment in business interactions is carried out to determine beforehand the occurrence ofundesirable events and their associated consequences. In the literature, various approaches have beenproposed by which an interaction initiating agent can ascertain the occurrence of undesirable event/s and determine their consequences in an interaction. But all of those approaches just consider those events that are related on the performance of the other agent, with whom the interaction initiating agent is forming an interaction with. It is possible that there are also such events that are not dependant on the other agent?s performance, but will directly or in-directly have an impact on the successful completion of the interaction. In this paper we will highlight the importance of considering such event/s during the process of risk assessment, and propose a methodology by which the interaction initiating agent can determine and quantify their effect on the successful completion of its business interaction.